(untitled) (Revista Argentina de Cirugía, 2026)
Background: Measuring quality in surgery through improvement interventions favors better patient outcomes and lower institutional costs. Textbook surgical outcome (TSO) and textbook oncologic outcome (TOO) are an organized way to measure the quality of surgical activity. Objective: The aim of the present study was to evaluate the proportion of patients with low rectal cancer who underwent abdominoperineal amputation by the same surgical team and achieved the TSO and TOO. Material and methods: We conducted a descriptive observational study based on the retrospective review of TSO and TOO parameters in patients undergoing abdominoperineal amputation for rectal cancer, between August 2015 and March 2023. The percentage of patients who achieved the TSO and TOO was estimated. Results: A total of 26 patients were included; mean age was 52.07 years and 18 (69.2%) were men and 25 patients (96%) received neoadjuvant therapy. The TSO was achieved in 20 patients (76.9%); 14 patients (53.8%) achieved the TOO and 13 patients (59%) achieved both textbook outcomes. The presence of complications and < 12 lymph nodes resected were the most common reasons for not achieving 100% of both textbook outcomes; other items were R0 resection, length of hospital stay and readmission. Conclusion: Fifty percent of patients with abdominoperineal amputations achieved an adequate TSO and TOO. The analysis allows us to understand where we must take action in order to improve the quality of our results.